QUALITY CONTROL ANALYSIS ON PRODUCTION PROCESS OF GARMENT AT GOLDEN FLOWER LLC UNGARAN - Naufal Nadhif, Kevin; Kusumawardhani, Amie (Diponegoro Journal of Management, 2021)
The aim of doing this study is to analyze how the implementation of quality control at PT. Golden Flower Ungaran in an effort to control the level of product damage. The data was collected by interviewing, observing, and documenting, followed by processing it using the Statistical Quality Control method. includes filling in the examination sheet, making histograms, making Pareto diagrams, making and calculating control charts, making causal diagrams. The results of this study indicate that the types of damage that occur in garment production are caused by Broken stitch, Skipped stitches, Obras oblique / untidy, Ironing and Dirty. From the cause-and-effect diagram, it can be seen that the factors that cause product damage are derived from material factors, machines, methods and employees. The use of the p control chart shows that the product quality control process is still outside the control limit because there are still four points that are outside the upper control limit and the lower control limit, thus indicating that the quality control process has not been carried out properly.